Validation of the medium and short version of CENSOPAS-COPSOQ: a psychometric study in the Peruvian population - Martha R. Lucero-Perez; Iselle Sabastizagal; Jonh Astete-Cornejo; Miguel Angel Burgos; David Villarreal-Zegarra; Salvador Moncada (BMC, 2022)
Abstract Background The presence of psychosocial risks at work are associated with mental and physical health issues in workers. The study aim was to adapt the COPSOQ-ISTAS21 (Spanish version of the Copenhagen Psychosocial Questionnaire and Union Institute of Work, Environment and Health) Medium-Version to the Peruvian context and to develop a Short-Version of the instrument. Method Cross-sectional design study. The COPSOQ-ISTAS21 Medium Version was used. A confirmatory factor analysis was performed to determine the internal structure of each subdimension (first-order) and dimension (second-order) using the Robust Maximum Likelihood estimation method, and classic fit indices in the literature (CFI, SRMR, RMSEA). Internal consistency was evaluated using the alpha and omega coefficients. A short version was developed based on the items with the highest factorial load and that reduce the factorial complexity. Results A total of 1707 participants were evaluated. In the confirmatory factor analysis, the goodness-of-fit indices for seventeen of the 20 one-dimensional models (subdimensions) were identified; two subdimensions could not be evaluated because they presented only two items. When conducting a multidimensional analysis, we identified that all second-order models presented optimal goodness-of-fit indices, except "psychological demands at work". Finally, a short version of only 31 items was designed from the items with optimal fit indices. Conclusions The new adapted versions of COPSOQ-ISTAS21 were renamed CENSOPAS-COPSOQ (National center of occupational health and environment protection for health -in Spanish- and Copenhagen Psychosocial Questionnaire). The CENSOPAS-COPSOQ is an instrument with sufficient evidence of validity and reliability in its medium and short version, which is why its use is recommended in Peruvian work centers to identify the evaluation and prevention of psychosocial risks at work in Peru.